Inflammatory Response Patterns in ICSI Patients: A Comparative Study Between Chronic Anovulating and Normally Ovulating Women - Lamaita, Rivia Mara; Pontes, Anaglória [UNESP]; Belo, Andrezza V.; Caetano, Joao Pedro J.; Andrade, Silvia P.; Candido, Eduardo Batista; Traiman, Paulo [UNESP]; Carneiro, Marcia Mendonca; Silva-Filho, Agnaldo L. [UNESP] (Sage Publications Inc, 2012)
The aim of this study was to evaluate inflammatory response in chronic anovulating infertility women undergoing intracytoplasmic sperm injection. Thirteen infertile women with chronic anovulation and 23 normally ovulating women were prospectively evaluated. N-acetylglucosaminidase (NAG), myeloperoxidase (MPO), monocyte chemoattractant protein 1 (MCP-1), and C-reactive protein (CRP) concentrations were evaluated in serum and follicular fluid. Women with chronic anovulation presented higher NAG and MPO activity in follicular fluid when compared with normally ovulating women. Serum MPO activity was higher in the control group compared to the chronic anovulation group. Both serum and follicular fluid CRP concentrations were higher in women with chronic anovulation in comparison with the control group. Higher MCP-1 follicular fluid concentrations and serum levels of CRP were associated with the occurrence of ovarian hyperstimulation syndrome. Patients with chronic anovulation exhibited significantly higher follicle macrophage/neutrophil activation as well as unspecific inflammatory response by comparison with normally ovulating women.
Keywords: infertility; chronic anovulation; intracytoplasmic sperm injection (ICSI); inflammatory response; N-acetylglucosaminidase; myeloperoxidase; CRP